EVALUASI KEBERLANJUTAN IMPOR BERAS KE INDONESIA UNTUK KESTABILAN BISNIS ARCONEL DI MASA DEPAN - Akhmad Faizal Nasution; Harimukti Wandebori (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Indonesia’s rice import is centralized under Bulog, a state-owned company, as the only rice importer in Indonesia. In this research, a Japanese trading company named Arconel is competing in Bulog’s rice tender in 2024. Arconel’s long experience in rice trading is not reflected in Indonesia’s rice import business. Their total tender award volume is low compare to Bulog’s total import quantity in 2024. This condition raise concern about its competitiveness and sustainability in the Indonesian market. This research is conducted to evaluate whether its current business model and capabilities are sufficient to compete in Indonesia’s rice market. This research combines several analytical tools: Porter’s Five Forces, the Resource-Based theory, PESTEL analysis, thematic analysis of interview data from several stakeholders, SWOT analysis, and TOWS matrix. A focused cost leadership strategy is recommended for Arconel to compete in Bulog tender. The proposes implementation plan includes investing in other rice processing facility, negotiate long-term contracts with trusted suppliers, and improve internal process between HQ and branch offices. This research offer insight for Arconel to remain competitive in government-controlled markets dominated by producers and vertically integrated players.